2021
DOI: 10.5812/aapm.112540
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ultrasound-Guided Supra-scapular Plus Axillary Nerve Block with Interscalene Block for Postoperative Pain Management in Arthroscopic Shoulder Surgery; A Double-Blinded Randomized Open-Label Clinical Trial

Abstract: Background: Post-arthroscopic shoulder surgery pain is severe enough to interfere with initial recovery and rehabilitation. Objectives: We aimed to evaluate the analgesic effects of postoperative ultrasound-guided suprascapular plus axillary nerve blocks superficial subepidermal axon bundles (SSAB) with interscalene block (ISB) in arthroscopic shoulder surgery. Methods: In this single-blind randomized, open-label clinical trial, 80 candidates of elective arthroscopic shoulder surgery were randomly allocated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…With the rapidly growing number of surgeries being performed in an ambulatory setting, regional blockade is increasingly used as a modality for controlling pain while reducing common side effects of opioid-centered analgesia (1)(2)(3)(4). The addition of adjuvants to local anesthetics for nerve block prolongation is a common practice in regional anesthesia (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…With the rapidly growing number of surgeries being performed in an ambulatory setting, regional blockade is increasingly used as a modality for controlling pain while reducing common side effects of opioid-centered analgesia (1)(2)(3)(4). The addition of adjuvants to local anesthetics for nerve block prolongation is a common practice in regional anesthesia (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 2 regional anesthetic techniques are required to establish effective pain management in patients with clavicle fractures (11). Previous studies have suggested a combination of superficial cervical plexus block with interscalene block seeking the same aim (7,(12)(13)(14). This combination is not only timeconsuming, but also has its own complications, including phrenic nerve palsy, Horner syndrome, and vocal cord paralysis (15).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, multiple approaches are available to manage clavicular fractures, including general anesthesia or regional techniques such as interscalene brachial plexus combined with superficial cervical plexus blockade (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound guidance aids in real-time visualization of the needle and the relevant anatomy (e.g. brachial plexus blocks) ( 20 , 21 ). When compared to nerve stimulation, ultrasound guidance for brachial plexus block has been shown to improve efficiency and block success, reduce complications like vascular puncture and local anesthetic systemic toxicity ( 22 ).…”
Section: Contextmentioning
confidence: 99%